AB0333 CLINICAL AND ULTRASONOGRAPHIC RESPONSE TO SUBCUTANEOUS METHOTREXATE IN EARLY RHEUMATOID ARTHRITIS. PRELIMINARY RESULTS. (13th June 2020) - Caballero Motta, L. R.; Anzola Alfaro, A. M.; Torrens Cid, L. A.; Soleto, C. Y.; Serrano Benavente, B.; Janta, I.; Molina Collada, J.; Gonzalez, C.; Monteagudo, I.; Alvaro Gracia, J. M.; Nieto, J. C.
Abstract : Background: Metotrexate (MTX) is usually the first line therapy for Rheumatoid Arthritis (RA) because of its favorable efficacy-toxicity ratio. However the exact mechanism and treatment response time in both a clinical and ultrasonographic setting are still uncertain. Objectives: To describe the clinical and ultrasound response to MTX during the first 6 months of treatment in early RA patients who started subcutaneous methotrexate as the first disease-modifying drug (DMARD). Methods: Ongoing prospective cohort of patients with early RA (ACR-EULAR 2010 criteria), over 18 years and starting MTX-SC. Patients had a clinical and ultrasonographic evaluation at baseline, 1, 3 and 6 months. We collected demographic data, C-reactive protein [CRP], erythrocyte sedimentation rate [ESR], rheumatoid factor [FR], anti-citrullinated protein antibody [ACPA]), inflammatory activity indexes (DAS28esr and DAS28crp) and EULAR's response to treatment (delta value of -1.2 in DAS28 scores). Joints explored with ultrasound were elbows and wrists (radio-carpal and inter-carpal joint) counted as a single joint, 1st-5th metacarpophalangeal (MCF), proximal interphalangeal (IFP), knees, tibio-talar and subtalar joints and 2nd-5th metatarsophalangeal (MTF) joints. Bone erosions were evaluated in 2nd and 5th MCF, styloid, distal ulna and 5th MTF. Synovitis was graduated semi-quantitatively from 0 to 3 (OMERACT) and calculated on B mode and Doppler. Results: 35 patients were included (mean age 61.2 years, 65.7% women) with a median of 0.8 (+/-8) months delay to diagnosis. 34 patients (97.1%) started 15mg MTX-SC/weekly. A higher DAS28esr was found in baseline data for the group that had a response by month 1 (DAS28esr baseline 5.5 vs 4.2 p=0.01), no other significant differences were found. During the first month, a significant response was achieved in 13 (41%) patients and remission in 11 (35%) (Table 1 ). 17 patients have 6 th month data. 11 (64.7%) have achieved EULAR response compared to baseline(P=0.0005) out of which 7 (54.5%) had already reached it by month 1. A difference in MTX dose (month1 14.8 vs month6 17.1 p=0.003) was found between month 1 and 6, with no differences in disease activity. In the ultrasonographic baseline data; 8 patients (22.9%) had erosions, with a mean of 2, 75 erosions/patient (22 of the 280 locations). During the follow up the global rating lowered, with no differences in B mode but significant differences in Doppler at the 6 month mark (Table 2 ). As of this report, 10 patients (28.5%) had stopped MTX treatment due to lack on response or adverse effects and 8 (22.9%) are waiting 6 th month evaluation. Conclusion: In this cohort half of the patients that responded to treatment had achieved this by month 1. A higher baseline inflammatory profile was related to the response. Little difference is found between month 1 and 6 on clinical data, however ultrasonographic results suggest that at least 6 months are needed for Doppler improvement. Perhaps MTX has a faster effect over joint pain and lowers DAS28 scores requiring longer to completely suppress inflammatory activity. References: [1]Braun, J. et al. Comparison of the clinical efficacy and safety of subcutaneous versus oral administration of methotrexate in patients with active rheumatoid arthritis. Arthritis Rheum 2008 Disclosure of Interests: Liz R. Caballero Motta: None declared, Ana Melissa Anzola Alfaro: None declared, Luis A Torrens Cid: None declared, Christian Y Soleto: None declared, Belén Serrano Benavente: None declared, Iustina Janta: None declared, Juan Molina Collada: None declared, Carlos Gonzalez Consultant of: Gilead, Janssen, Novartis, , Speakers bureau: Abbvie, Celgene, Gilead, Janssen, Novartis, Pfizer, Roche, Indalecio Monteagudo: None declared, Jose Maria Alvaro Gracia: None declared, Juan Carlos Nieto Speakers bureau: Pfizer, Abbvie, MSD, Novartis, Janssen, Lilly, Nordic Pharma, BMS, Gebro, FAES Farma, Roche, Sanofi